2016
DOI: 10.1136/bmjopen-2015-009669
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical administration of combined hyaluronic acid (HA) and chondroitin sulfate (CS) for the treatment of female recurrent urinary tract infections: a European multicentre nested case–control study

Abstract: ObjectivesTo compare the clinical effectiveness of the intravesical administration of combined hyaluronic acid and chondroitin sulfate (HA+CS) versus current standard management in adult women with recurrent urinary tract infections (RUTIs).SettingA European Union-based multicentre, retrospective nested case–control study.Participants276 adult women treated for RUTIs starting from 2009 to 2013.InterventionsPatients treated with either intravesical administration of HA+CS or standard of care (antimicrobial/immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…Recently, a case‐control study showed that intravesical instillation of a HA/CS mixture significantly reduced the recurrence rate in women with recurrent UTIs . Moreover, the study by Raymond et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case‐control study showed that intravesical instillation of a HA/CS mixture significantly reduced the recurrence rate in women with recurrent UTIs . Moreover, the study by Raymond et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely used for the prevention of rUTIs, the clinical evidence for the use of exogenous GAG‐layer analogs in this population is predominantly limited to retrospective series with heterogeneity in terms of the intravesical formulation used and the frequency and duration of therapy. Despite reporting promising results in terms of reduction in rUTI rates compared with antibiotic prophylaxis, limitations exist regarding the method of defining and diagnosing infections and the retrospective nature of these studies limits their applicability . However, two RCTs have reported promising results.…”
Section: The Role Of Glycosaminoglycan Layer In the Prevention Of Rutimentioning
confidence: 99%
“…Despite reporting promising results in terms of reduction in rUTI rates compared with antibiotic prophylaxis, limitations exist regarding the method of defining and diagnosing infections and the retrospective nature of these studies limits their applicability. [47][48][49] However, two RCTs have reported promising results. In one study, intravesical hyaluronic acid plus chondroitin sulfate was compared with placebo (normal saline), in 57 women with rUTI.…”
Section: Glycosaminoglycan Layer In the Prevention Of Rutimentioning
confidence: 99%
“…A total of 276 women with rUTIs were treated with intravesical hyaluronic acid and chondroitin sulfate and achieved significantly reduced rates of recurrence and increased symptomatic relief, quality of life and bladder capacity compared to standard therapy only (98). Standard therapy in this study consisted of an antimicrobial, immunoactive prophylaxis, probiotics and cranberry.…”
Section: Intravesicalmentioning
confidence: 99%